THE MOOD OF THE PERIOD IN THE NOVEL" REBELLION AND OBEDIENCE" AND THE HUMAN SPIRIT - Toshpulatova, Dilorom (Журнал иностранных языков и лингвистики, 2021)
This article is about the mood of the period in the novel “Rebellion and obedience” and the Human Spirit.